Greedy Algorithm-Based Energy Management Method for Battery Energy Storage Station - Wang, Weizhou; Han, Xushan; Wu, Yue; Li, Hanning; Li, Xiangjun; Jia, Xuecui (2021 IEEE Sustainable Power and Energy Conference (iSPEC), 2021)
With the rapid development of renewable energy resource(RES) in recent years, battery energy storage system (BESS) is more and more widely used in power system. The inconsistency of single battery will have a great impact on the operation of the whole battery pack. At the same time, with the increase of the service time of the battery pack, this inconsistency will become greater and greater. Therefore, some strategies should be adopted for the energy management of BESS. Existing studies have not fully considered the operation efficiency of power conversion system (PCS). In this paper, the greedy algorithm model is being used to carry out the dynamic optimization process aiming at improving the consistency of battery state of charge (SOC). The experimental results show that greedy algorithm proposed in this paper can achieve good SOC consistency control.